Socioeconomy Conditions After The Development of Toll Roads in Salatiga - Grace Natalia Marpaung; Etty Soesilowati; Yozi Aulia Rahman; Yustiko Arvan Gilang Pangestu; Tania Wicaksana (Economics Development Analysis Journal, 2021)
In Central Java, one of supporting factors of regional economic growth viewed from regionalfacilities and infrastructures is toll road facilities. Transjawa toll road is a network that connectsseveral cities in Java. Particularly, this toll road connects two biggest cities in Indonesia, namelyJakarta and Surabaya in which Salatiga is also one of cities traversed by this toll. This ±1.000 kmtoll road continues the previous toll roads that have existed, including Merak – Cikampek, Jakarta– Bandung, Semarang – Bawen, and Surabaya – Pandaan. Despite the positive impacts, Transjawatoll road also gives negative impacts for local communities. Thus, this study aimed (1) to find outthe socioeconomic condition of farmers after Transjawa toll road construction in Salatiga and (2)to find out the socioeconomic condition of Micro, Small, and Medium Enterprises (MSMEs) afterTransjawa toll road construction in Salatiga. This study used qualitative and quantitative datataken from from 30 main respondents. The construction of transjawa toll road in Salatiga regionbrings good effects. It was proved by the better condition of socioeconomic and income of farmersand MSME doers in Salatiga region after the construction of this toll road.